Effect of Prepregnancy Alcohol Consumption on Postpartum Relationship Satisfaction and Divorce among Norwegian Mothers - Sonja Mellingen; Torbjørn Torsheim; Frode Thuen (SAGE Publishing, 2015)
This study assessed the effect of prepregnancy level of alcohol use among mothers on relationship breakups with young children at 36 months after birth and the extent to which relationship satisfaction (RS) throughout the postpartum period could mediate any association between alcohol use and divorce. The data were part of the Norwegian Mother and Child Cohort Study, and analyses of the present article were based on a total of 69,117 mothers divided into low-, medium-, and high-risk consumption groups. All the three groups experienced a decrease in RS, but the largest effect was observed for the high-risk group. Mothers in this group had 55% higher odds for divorce as compared to the low-risk group. The findings supported a conceptual model whereby the effects of alcohol use on divorce were mediated through lowered RS.